Problematic Idiosyncrasies: Rediscovering the Historical Context of D Arcy Wentworth Thompson S Science of Form - Esposito-Varriale, M (2014)
D Arcy Thompson has often been portrayed as a loner. His science of form has frequently been labeled anachronistic, idiosyncratic, and unconnected to his contemporary biology. This article aims to challenge this interpretation. Thompson s representation as a loner did not lie in the idiosyncrasies of his science, but in our own historiography. Through the use of unedited archival sources, this study shows that Thompson s biology was well-connected to an international research program - a program mainly shared by developmental biologists, physiologists, and morphologists. In addition, this article also aims to propose a new interpretation of Thompson s On Growth and Form. Drawing on his private correspondence and published sources, the paper re-contextualizes the contents and conclusions of Thompson s seminal work. We will see that Thompson defended a particular kind of organismal biology. The bio-science he supported stemmed not only from Aristotle s zoology or Pythagorean mathematics, but had many allies among twentieth-century naturalists. Copyright © Cambridge University Press 2014.